If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/7(u-2)=-1/2(2u-5)
We simplify the equation to the form, which is simple to understand
2/7(u-2)=-1/2(2u-5)
Simplifying:
+ 0.285714285714*(u-2)=-1/2*(2u-5)
Simplifying:
+ 0.285714285714*(u-2)=-0.5*(2u-5)
Reorder the terms in parentheses
+( + 0.285714285714u-0.571428571429)=-0.5*(2u-5)
Remove unnecessary parentheses
+ 0.285714285714u-0.571428571429=-0.5+*(+2u-5+)
Reorder the terms in parentheses
+ 0.285714285714u-0.571428571429=+(-1u+2.5)
Remove unnecessary parentheses
+ 0.285714285714u-0.571428571429=-1u+2.5
We move all terms containing u to the left and all other terms to the right.
+ 0.285714285714u+1u=+2.5 + 0.571428571429
We simplify left and right side of the equation.
+1.28571428571u=+3.07142857143
We divide both sides of the equation by 1.28571428571 to get u.
u=2.38888888889
| 7x+5x+6x=180 | | 2n+4(-1-7n)=-40-8n | | 18=7+5(f+9) | | x=14-3y | | 2p+7p=56 | | 7x+5x+6x= | | x+90=x+32 | | -30=x+-10+11x | | x/4-1/6=12 | | 7y+5=54 | | -5+2(5x-7)=7(x+2) | | z+6=2x-3 | | 8c+12=56 | | r=7/8(p+7q) | | -4*6-5=c | | 4-b=12 | | 6(5c+9)=28-3c | | 16-3+(-7)-(-13)= | | 3-w=2sr+20 | | 1/2(32z^3-10) | | -8r+6(2-5r)=-6(1-4r) | | g+(-1/5)=-3/10 | | 40=5x+-8 | | g+(-1/5)=-(3/10) | | 3/4(d-3)=6 | | 2x-8=6x+24 | | 5x+12=28-3x | | 15p^2+40p=0 | | 6p^2=-31-5 | | 10+x+-17x=4 | | (3x-4)(4x-3)-(2x-7)(3x-2)=214 | | 3x+0.5y=5 |